Local Newspaper Strategy to Survive in the Digital Era - Hendra Alfani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
The development of communication and information technology that gave birth to the digital era has made the competition for the mass media industry increasingly competitive. This condition requires conventional mass media, especially local newspapers to carry out special strategies focused on efforts to transform their activities in accordance with the demands of the times, so as not to get further behind with new media that use the internet and digital technology. The Daily OKU Ekspres and OKU Timur Pos, as conventional local newspapers, are confronted with this reality. Surrender or immediately develop a strategy for transformation and change, in order to remain able to compete in the media industry. This study uses a qualitative method, where data analysis is displayed descriptively. The results showed that the two newspapers systematically implemented four strategies to face competition with online media, namely; strengthen local content with investigative reports, media convergence, penetration in social media networks and carry out regular and incidental off-air activities. In the context of this strategy choice, the two newspapers are able to capitalize on the vulnerability of online media to strengthen their existence.